2015
DOI: 10.3390/soc5020537
|View full text |Cite
|
Sign up to set email alerts
|

Complexity and Volume: An Inquiry into Factors that Drive Principals’ Work

Abstract: Background: The work of contemporary school principals is intensifying in terms of its complexity and volume. Many factors moderate and drive such work intensification. This study aims to understand what and how factors interact to complicate principals' work. Methods: Focus groups and an online survey were used for data collection. Three focus group sessions with eight principals were conducted to help develop and refine the online survey. The survey covers 12 key areas in principals' work and was distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 48 publications
1
40
0
Order By: Relevance
“…For example, Ontario principals are expected to build relationships and develop people by providing support and demonstrating consideration for individual staff members; stimulating growth in the professional capacity of staff; building trusting relationships with and among staff, students, and parents; and establishing productive working relationships with teacher federation representatives (Ontario Leadership Framework, 2013). We know from our research that, in terms of the people with whom principals spend their time, 70.7% of principals indicated that they have high or very high levels of interaction with classroom teachers (Pollock et al, 2015). It surprised us that teachers were not ranked higher on the list; this led us to infer that the amount of time principals spend with a particular stakeholder group does not determine the degree to which they feel accountable to said group.…”
Section: Discussionmentioning
confidence: 78%
“…For example, Ontario principals are expected to build relationships and develop people by providing support and demonstrating consideration for individual staff members; stimulating growth in the professional capacity of staff; building trusting relationships with and among staff, students, and parents; and establishing productive working relationships with teacher federation representatives (Ontario Leadership Framework, 2013). We know from our research that, in terms of the people with whom principals spend their time, 70.7% of principals indicated that they have high or very high levels of interaction with classroom teachers (Pollock et al, 2015). It surprised us that teachers were not ranked higher on the list; this led us to infer that the amount of time principals spend with a particular stakeholder group does not determine the degree to which they feel accountable to said group.…”
Section: Discussionmentioning
confidence: 78%
“…Research that investigates principals’ work intensification and their coping strategies generally uses a quantitative survey research design (Alberta Teachers’ Association [ATA], 2017; Pollock et al, 2014, 2015, 2017; Riley, 2016). There is a lack of qualitative research that allows for the data to have an enhanced level of details and complexities to glean further insights into the phenomenon.…”
Section: Methodsmentioning
confidence: 99%
“…A plethora of research makes clear that school principals work under extremely stressful conditions and constantly struggle to cope with their work intensification (Alberta Teachers’ Association [ATA], 2017; Darmody & Smyth, 2016; Leithwood & Azah, 2014; Pollock et al, 2014, 2015, 2017; Riley, 2016). Work intensification refers to how hard and fast principals are working in any given period (Fein et al, 2017).…”
Section: Work Intensificationmentioning
confidence: 99%
“…Drysdale et al (2016) claim that the nature of school leaders' work is changing and that this leads to complications. Pollock et al (2015) provide evidence of the full extent of the nature of school leaders' work and focus on particular aspects of the role, such as leadership (Gurr 2015;Leithwood, Patten & Jantzi 2010), trust (Tschannen-Mora & Gareis 2015 and the interactive nature of administrative work (Spillane 2015). In this way, they provide a more accurate picture of school leaders' work.…”
Section: Long-term School Leadership In Sweden Compared To Other European Countriesmentioning
confidence: 99%